2017
DOI: 10.1177/0004867417721654
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the angiotensin system improves mental health domain of quality of life: A meta-analysis of randomized clinical trials

Abstract: Use of angiotensin blockers and inhibitors for the treatment of hypertension in otherwise healthy adults is associated with improved mental health domains of quality of life. Mental health quality of life was a secondary outcome in the included studies. Research specifically designed to analyse the usefulness of drugs that block the angiotensin system is necessary to properly evaluate this novel psychiatric target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 92 publications
2
29
0
Order By: Relevance
“…Examples include statins, aspirin and angiotensin antagonists 788, 789, 790, 791, 792, 793. The implications are that clinicians should be actively engaged in the management of these disorders, and should select therapies from those agents that may have benefit in mood symptoms.…”
Section: Specific Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include statins, aspirin and angiotensin antagonists 788, 789, 790, 791, 792, 793. The implications are that clinicians should be actively engaged in the management of these disorders, and should select therapies from those agents that may have benefit in mood symptoms.…”
Section: Specific Populationsmentioning
confidence: 99%
“…Clozapine and olanzapine are associated with the greatest level of risk, followed by quetiapine (particularly in higher doses) and risperidone, with a more minimal impact of aripiprazole, ziprasidone, asenapine, and lurasidone 810. Lithium and divalproex are also associated with weight gain 791. All patients on atypical antipsychotics should be monitored for changes in blood glucose and lipid profiles as indicated previously in this section, and if disturbances are detected, the atypical antipsychotic should be discontinued if possible and appropriate treatment initiated if necessary.…”
Section: Safety and Monitoringmentioning
confidence: 99%
“…There may have been a lack of adequate power to demonstrate such an association as we have already reported a lower incidence of new-onset diabetes as well as improved quality of life among individuals randomized to receive the ACEI-based regimen (Chowdhury et al, 2015). Recently, Brownstein et al in a meta-analysis of randomized clinical treatment trials in hypertensive patients showed that use of these ACEI-based regimens was associated with an improved mental health domain of quality of life scales (Brownstein et al, 2018).…”
Section: Physical Activities (In Two Weeks Prior Randomization)mentioning
confidence: 88%
“…Similarly, an association between depression and angiotensin converting enzyme (ACE) polymorphisms has also been reported (Ancelin et al, 2013). In addition, people taking either ACEIs or angiotensin receptor blocking agents (ARBs) as antihypertensive drugs may have improved quality of life (Brownstein et al, 2018). Thus, the relationship between agents blocking the reninangiotensin system and depression requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The lower rate of adverse events and the perception of health benefit from the treatment add up to potential psychotropic effects that have been described in RAAS blockers. A recent meta-analysis indicates that treatment of healthy adults with hypertension with ACEIs or ARBs is associated with improved mental health quality of life, although this was a secondary outcome in the included studies and thus the benefit may only be hypothesized [14].…”
Section: Angiotensin Receptor Blockers and Angiotensin Converting Enzmentioning
confidence: 99%